Targeting Peritumoral Lesions Identified by Computed Tomography and Magnetic Resonance Imaging in Feline Injection-Site Sarcomas for Microscopic Examination. Issue 5 (September 2021) - Löhr, Christiane V.; Stieger-Vanegas, Susanne M.; Terry, Jesse L.; Milovancev, Milan; Medlock, Jan
Peritumoral lesions identified during in vivo imaging of feline injection-site sarcoma (FISS) are frequently interpreted as neoplastic. We recently showed that most peritumoral imaging-identified lesions (PTIILs) in FISS are non-neoplastic. In this article, we describe a protocol to target PTIIL for microscopic examination and report on the protocol's performance. Ten client-owned cats with FISS were prospectively enrolled. A fiducial marker sutured onto the skin, centered on the palpable mass, served as reference point throughout the study. Each FISS and surrounding tissue was imaged in vivo by dual phase computed tomography angiography and multiple magnetic resonance imaging pulse sequences and each PTIIL documented. Subgross measurements obtained during trimming aided localization and identification of PTIIL during microscopy. Histologic findings were categorized by descending clinical relevance: neoplastic, equivocal, non-neoplastic, within normal limits (WNL). Based on in vivo imaging resolution limits, histologic findings were ≥3 mm in at least one dimension and ≥3 mm apart. Surgical margins served as control tissue for PTIILs. Eighty-one of 87 PTIIL were examined histologically; 13 were neoplastic, 16 equivocal, and 28 non-neoplastic; 24 had no identified histologic correlate. Two neoplastic and 10 equivocal findings were located outside of PTIILs but none of them were located in sections of surgical margins. Computation of a simple confusion matrix yielded fair sensitivity (70.4%) and low specificity (59.7%) for prediction of PTIIL by histologic findings. After combining instances of normal microanatomy with non-neoplastic histologic findings, specificity increased (85.1%) and sensitivity decreased (35.8%). The protocol is a blueprint for targeting PTIIL for microscopic examination but may benefit from further refinement.